2009
DOI: 10.1021/bm9007937
|View full text |Cite
|
Sign up to set email alerts
|

Biobased Polymer System: Miniemulsion of Poly(alkyl methacrylate-graft-lactic acid)s

Abstract: To broaden the application scope of lactic acid polymers, a new miniemulsion of poly(alkyl methacrylate-graft-lactic acid)s has been developed. The graft copolymer synthesis was based on a poly(lactic acid) macromonomer having a methacryloyl polymerizable group. The macromonomer and a comonomer of n-butyl methacrylate together with a suitable surfactant formed a miniemulsion of the comonomers in water. A radical copolymerization of the comonomers took place to produce the graft copolymer as a stable miniemulsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 34 publications
1
48
0
Order By: Relevance
“…As previous our reports [30,31], PLA macromonomer derived from HEMA was obtained by ring-opening polymerization of lactides, of which the rate of functional group is >98% by NMR analysis and the degree of polymerization is from 4 to 10 by ESI-TOF-MS measurement.…”
Section: Synthesis Of Pla Macromonomer Modified With Hemamentioning
confidence: 79%
See 3 more Smart Citations
“…As previous our reports [30,31], PLA macromonomer derived from HEMA was obtained by ring-opening polymerization of lactides, of which the rate of functional group is >98% by NMR analysis and the degree of polymerization is from 4 to 10 by ESI-TOF-MS measurement.…”
Section: Synthesis Of Pla Macromonomer Modified With Hemamentioning
confidence: 79%
“…PLA macromonomer with ring-opening polymerization of lactide (lactide method) was synthesized as previous our report [30,31].…”
Section: Synthesis Of Pla Macromonomer Modified With Hemamentioning
confidence: 99%
See 2 more Smart Citations
“…The authors observed differences between the various polymers in terms of the particle size (range of 80-200 nm), size distribution and degradation time. Ishimoto et al (2009) [27] obtained nanoparticles through the miniemulsion copolymerization of poly(alkyl methacrylate-gra/i-lactic acid)s. The new bio-based polymer system allowed miniemulsions stable in water to be produced, which can be used, for example, in coating processes as a biomass-polymer material. The size distribution of the monomer droplets was measured by dynamic light scattering showing diameters in the range of 220-340 nm, depending on the surfactant used.…”
Section: Miniemulsion Polymerization Of Biodegradable Latexesmentioning
confidence: 99%